Study on the compacting device of combination for ridge-till and no-till planters. (October 2019) - Luo, Hongqi; Liu, Xia; Qin, Jiatong; Zhao, Guangwei
Abstract: Ridge tillage and conservation tillage combination is an important technology. The compacting device is one of the key components of no till planter. According to different agronomic requirements, a general type of combined type of pressing device was designed. In the device, the compacted wheel set should be designed, the ridge is compacted along the loose soil, and the ridging effect is enhanced. Meanwhile, the ring structure is designed on the compacting wheel to suppress the seeding belt. Through the force analysis and Simulation of the suppression device, the structural parameters are determined, and the adjustable mechanism is designed to realize the adjustability of the pressure of the town. By designing movable pressing ring, the number and size of the ring can be adjusted to meet the needs of different agronomic conditions. The modelling of combined press device is conducive to the promotion of no tillage seeding technique, which is a better combination of advantages of ridge tillage and conservation tillage.